중년남성 당뇨병 환자와 배우자의 성교육 프로그램 효과 연구 - 이화자(Lee Wha Ja); 김옥수(Kim Ok Soo) (Sŏngin Kanho Hakhoe chi, 2011)
Purpose: The purpose of this study was to evaluate the effects of a sex education program for middle aged men patients with diabetes and their spouses. Methods: The research design for this study was a non-equivalent control group quasi-experimental study. The subjects were 23 diabetic patients and their spouses with half of the subjects exposed to a structured sex education program. Sexual Beliefs and Information Questionnaire, Dyadic Sexual Communication Scale, Sexual Frequency Scale, Derogatis Sexual Function Inventory and International Index of Erectile Function-5 were used for data collection. Results: In the experimental group, sexual knowledge of diabetic patients and sexual communication with their spouses were improved after two weeks following the program. Also, in the experimental group, sexual knowledge, sexual communication, and sexual frequency in both diabetic patients and their spouses were improved after six weeks following the program. In the experimental group, sexual satisfaction of diabetic patients was improved after six weeks following sex education program, however their spouses in the experimental group showed no significant differences than those of the comparison group. Conclusion: The results of this study suggest that sex education program for both diabetic patients and their spouses could be utilized in public health centers, hospitals, and clinics.